Relationships between Knowledge, Attitudes and Practices of Food Safety and Hygiene among Culinary Students at UTHM - Hanif, Faruq; Zakariah, Siti Hajar (Research and Innovation in Technical and Vocational Education and Training, 2025)
Food safety and hygiene remains a growing concern in Malaysia, particularly within educational institutions where food handling often takes place. At Universiti Tun Hussein Onn Malaysia (UTHM), culinary students receive formal training in hygiene and food safety, yet their compliance with proper hygiene practices appears inconsistent. Although numerous studies have explored food safety and hygiene among UTHM students, few have applied the Knowledge, Attitudes, and Practices (KAP) framework to systematically examine behavioural outcomes. This study aims to examine the relationships between knowledge, attitudes, and practices (KAP) of food safety and hygiene among culinary students at UTHM. A quantitative survey was conducted involving 186 students, using a structured questionnaire. The data were analysed using descriptive and inferential statistics via SPSS software. The findings revealed that although students demonstrated moderate to high levels of knowledge and positive attitudes, their self-reported hygiene practices were inconsistent. Correlation analysis showed weak and statistically non-significant relationships between the three KAP components. These results suggest that knowledge and attitude alone may not lead to proper hygiene behaviour. This study recommends strengthening hands-on training, increasing supervision, and incorporating scenario-based learning strategies to improve food hygiene compliance among culinary students in TVET settings.